please solve this question with steps:
![\frac{x}{2} - \frac{x - 4}{6} = \frac{5}{3} \frac{x}{2} - \frac{x - 4}{6} = \frac{5}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%7D%7B2%7D+++-++%5Cfrac%7Bx+-+4%7D%7B6%7D++%3D++%5Cfrac%7B5%7D%7B3%7D+)
Attachments:
![](https://hi-static.z-dn.net/files/d3d/8ae35a1257ebcdd3ae68ac561a50113e.jpg)
sapna69:
listen
Answers
Answered by
6
Hey!
___________________________________________♦️
➡️![\frac{x}{2} - \frac{x - 4}{6} = 5 \frac{x}{2} - \frac{x - 4}{6} = 5](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%7D%7B2%7D+-+%5Cfrac%7Bx+-+4%7D%7B6%7D+%3D+5)
➡️![\frac{x - 2x}{2} = \frac{5}{3} + \frac{2}{3} = \frac{7}{3} \frac{x - 2x}{2} = \frac{5}{3} + \frac{2}{3} = \frac{7}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7Bx+-+2x%7D%7B2%7D+%3D+%5Cfrac%7B5%7D%7B3%7D+%2B+%5Cfrac%7B2%7D%7B3%7D+%3D+%5Cfrac%7B7%7D%7B3%7D+)
➡️![\frac{ - x}{2} = \frac{7}{3} \frac{ - x}{2} = \frac{7}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7B+-+x%7D%7B2%7D+%3D+%5Cfrac%7B7%7D%7B3%7D+)
➡️![+ x = - \frac{14}{3} + x = - \frac{14}{3}](https://tex.z-dn.net/?f=+%2B+x+%3D+-+%5Cfrac%7B14%7D%7B3%7D+)
Or
➡️![x = - \frac{14}{3} x = - \frac{14}{3}](https://tex.z-dn.net/?f=x+%3D+-+%5Cfrac%7B14%7D%7B3%7D+)
_________________________________________♦️
Hope it helps you!
___________________________________________♦️
➡️
➡️
➡️
➡️
Or
➡️
_________________________________________♦️
Hope it helps you!
Similar questions